A Novel Minimally Invasive Reduction Technique by Balloon and Distractor for Intra-Articular Calcaneal Fractures: A Report of 2 Cases - M. Prod’homme; S. Pour Jafar; P. Zogakis; P. Stutz (Case Reports in Orthopedics)
Treatment of displaced intra-articular fractures of the calcaneus remains a challenge for the orthopaedic surgeon. Conservative therapy is known to produce functional impairment. Surgical approach is plagued by soft-tissue complications and insufficient fracture reduction. We describe a minimally invasive technique that will hopefully improve these issues. We want to present our first experience through two cases. The first was a 46-year-old man who presented with a Sanders type IIBC calcaneal fracture, and the second was a 86-year-old woman with a type IIIBC calcaneal fracture. We introduced 2 Schanz screws in the talus and the calcaneus. After distraction, we introduced an inflatable balloon inside the calcaneus. By inflating the balloon, the articular surface was reduced by lifting it up. Then bone cement was injected in order to maintain the reduction. Additional screw fixation was used in the young patient. Postoperative imaging showed good congruence of the subtalar joint without leakage of cement, for the two cases. After 2 months, the patients had no pain and were without soft-tissue complications. We advocate this technique to perform a minimally invasive reduction and fixation of intra-articular calcaneal fractures because it preserves soft-tissues and provides good clinical results with early weight-bearing.